Genome-wide identification and expression analysis of C3H gene family in melon - Zheng, Ling; Dai, Haifang; Mu, Yuanfang; Li, Jinbo; Cheng, Yanwei; Han, Jianming (Frontiers in Plant Science, 2025)
Zinc finger protein (ZFP) represent a significant class of transcription factors in plants, involved in various functions, including tissue development, signal transduction, and responses to both biotic and abiotic stresses. ZFPs are categorized into 10 distinct subfamilies, among which the C3H gene family is recognized as a functionally significant group of transcription factors.To date, no studies have been reported regarding the C3H gene family in melon (Cucumis melo). In this study, 38 CmC3H genes were identified in the melon genome, and these genes are unevenly distributed across the 12 chromosomes. Phylogenetic analysis classified the C3H family members into four groups, with significant differences observed in sequence, protein motifs, and gene structure among CmC3H genes within the same group. The CmC3H family contains one pair of segmentally duplicated genes and shares 20, 7, 39, and 38 pairs of homologous C3H genes with Arabidopsis thaliana, rice (Oryza sativa), cucumber (Cucumis sativus), and watermelon (Citrullus lanatus), respectively. Promoter region analysis revealed a high abundance of cis-elements associated with growth and development, hormone regulation, and stress responses. Expression profiling revealed that CmC3H family members exhibit significant tissue-specific expression patterns. Quantitative PCR analysis indicated that six genes (CmC3H4, CmC3H7, CmC3H13, CmC3H24, CmC3H33, and CmC3H38) may play roles in melon’s drought stress resistance. Heavy metal lead stress appears to suppress the expression of CmC3H genes. The genes CmC3H24 and CmC3H33 may be involved in regulating melon’s resistance to Fusarium wilt infection. CmC3H11 and CmC3H21 can be considered as the key candidate genes for improving the melon’s ability to resist both biotic and abiotic stresses.This study provides preliminary insights into the expression profiles of CmC3H genes under drought stress, heavy metal lead stress, and Fusarium wilt infection, offering a theoretical foundation for the molecular mechanisms underlying melon improvement and stress resistance.